2016
DOI: 10.1038/srep37336
|View full text |Cite
|
Sign up to set email alerts
|

5-HTR3 and 5-HTR4 located on the mitochondrial membrane and functionally regulated mitochondrial functions

Abstract: 5-HT has been reported to possess significant effects on cardiac activities, but activation of 5-HTR on the cell membrane failed to illustrate the controversial cardiac reaction. Because 5-HT constantly comes across the cell membrane via 5-HT transporter (5-HTT) into the cytoplasm, whether 5-HTR is functional present on the cellular organelles is unknown. Here we show 5-HTR3 and 5-HTR4 were located in cardiac mitochondria, and regulated mitochondrial activities and cellular functions. Knock down 5-HTR3 and 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Specifically, activation of P2Y1 stimulates mitochondrial Ca 2+ uptake whereas activation of P2Y2 inhibits this process in hepatocytes (49). In cardiomyocytes, activation of 5HT 4 receptors also decreases mitochondrial Ca 2+ uptake and in turn, respiratory chain activity and ATP production (50). Melatonin, as a small, lipophilic ligand, is found in high levels in mitochondria where it can activate MT 1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, activation of P2Y1 stimulates mitochondrial Ca 2+ uptake whereas activation of P2Y2 inhibits this process in hepatocytes (49). In cardiomyocytes, activation of 5HT 4 receptors also decreases mitochondrial Ca 2+ uptake and in turn, respiratory chain activity and ATP production (50). Melatonin, as a small, lipophilic ligand, is found in high levels in mitochondria where it can activate MT 1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that soluble adenylyl cyclase protein kinase A (sAC-PKA) signaling inside mitochondria regulates ATP production and it also regulates mitochondrial Ca 2+ uptake [5, 6]. More recently, several G-protein coupled receptors that can use calcium as second messengers, such as cannabinoid receptors CB-1 [7], melatonin MT1 receptors [8], GABA B receptors [9], and 5-HT receptors 5- HTR4 [10] have been identified in the mitochondrial membranes. Therefore, in order to understand GPCR function in mitochondria and Ca 2+ -mediated cross-talk between GPCR activity and sAC-PKA signaling, it is essential to investigate optimal mitochondrial Ca 2+ concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even these larger integral membrane proteins can be translocated to mitochondria. One example concerns the serotonin receptor 5-HT 4 [27], which differs from the afore-mentioned ionotropic 5-HT 3 . In functional terms, the mitochondrial 5-HT 4 receptor was reported to decrease the respiration control ratio, contrary to 5-HT 3 , whereas the opening of the permeability transition pore was, again, found to be inhibited [27].…”
Section: Gpcrs In Mitochondriamentioning
confidence: 99%
“…One example concerns the serotonin receptor 5-HT 4 [27], which differs from the afore-mentioned ionotropic 5-HT 3 . In functional terms, the mitochondrial 5-HT 4 receptor was reported to decrease the respiration control ratio, contrary to 5-HT 3 , whereas the opening of the permeability transition pore was, again, found to be inhibited [27]. Particular insights were obtained by studies on the type-1 cannabinoid receptor CB 1 , which is also translocated to mitochondria [28][29][30][31].…”
Section: Gpcrs In Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation